Hypericum perforatum (ethanolic extract) ameliorates simulated hypobaric hypoxia induced oxidative stress and neuronal damage in brains of Balb/c mice - Gautam, Amardeep; Tabassum, Rizwana; Katyal, Anju (Asian Journal of Medical Sciences, 2018)
Background: Hypobaric hypoxia refers to lower oxygen availability at high altitudes and is the cause of high altitude illness. Drugs such as acetazolamide and dexamethasone provide symptomatic relief and are associated with undesired side effects. Plant extracts such as Hypericum perforatum, which are documented to have neuromodulatory role can be more beneficial in ameliorating high altitude illness. Aims and Objective: Progressive cognitive decline is the hallmark characteristic of hypobaric hypoxia induced neuropathology attributed to ensuing oxidative stress and subsequent hippocampal damage. We have explored the efficacy of ethanolic extracts of Hypericum perforatum in amelioration of hypobaric hypoxia induced oxidative stress and associated behavioral deficits in mice. Material and Methods: Male Balb/c mice were exposed to simulated altitude of 25,000 ft. for 7 days (6 hr. per day) in a specially designed chamber. Ethanolic extract of Hypericum perforatum (HPE)(25mg/kg of body weight) was given orally prior to hypoxia exposure and effects were compared to hypoxia and control groups. Results: Animals exposed to hypobaric hypoxia showed sign of cognitive deterioration at day 3 and day 7 in the Elevated Plus Maze and Passive Avoidance Step through behavioral paradigms as compare to normoxic animals. Administration of HPE was able to alleviate the amnesic effect in treatment group, indicated by reduction in transfer latencies at day 3(IR-3 = -0.66±0.07) and day 7 IR-7 = -0.81±0.06) in elevated plus maze task and increased passive avoidance step through latency at day 3, (IR-3 = 3.23±0.67),as compared to ±hypoxic mice. Hypoxia group of animals suffered significant oxidative stress compared to normoxic mice as indicated by up-regulated malondialdehyde and total nitrite levels in hippocampal homogenates. The plasma lactate dehydrogenase activity was also increased following hypoxia indicating tissue damage. Co-treatment with HPE in simulated hypobaric hypoxia insult for seven days resulted in significant reduction in malondialdehyde, total nitrites and plasma LDH levels in animals. Conclusion: Hypericum perforatum extract improves cognitive performance in hypobaric hypoxia exposed mice with a concomitant reduction in oxidative stress burden suggesting its plausible use for preventing high altitude illness. Asian Journal of Medical Sciences Vol.9(2) 2018 1-8